Incentivized for Leveling the Playing Field: Do State Economic Incentives Compensate for High Taxes?. Issue 2 (May 2020) - Cheng, Shaoming; Guo, Hai (David); Liu, Cathy Yang
State tax and nontax incentives have been widespread in the United States, though their efficacy in job creation and economic development has been repeatedly questioned in the literature by scholars and policy makers. Why, then, do states persistently pursue these incentive policies? Using the newly developed Panel Database on Incentives and Taxes, we adopt a dynamic spatial Durbin panel model to account for both temporal and spatial dependence and to shed light on this question. Empirical evidence suggests a statistically significant and positive relationship between tax credits and tax burdens (i.e., elevated tax breaks are used to offset higher tax differentials). States therefore may seek to create a level playing field in business attraction and retention by overcoming tax disadvantages. Besides, high-serial dependence is present in the use of various tax credits, suggesting a high self-perpetuating tendency that tax breaks, once introduced, are likely to be persistent over time. States are also found to be engaged both in spatial competition or imitation among geographically proximate states, and in strategic benchmarking among states that are geographically distant but economically alike.